1991
DOI: 10.1107/s0021889891003084
|View full text |Cite
|
Sign up to set email alerts
|

Structural modifications of highly porous silica aerogels upon densification

Abstract: Structural changes during isothermal sintering were studied for two base-catalyzed SiO2 aerogels with initial densities p~ = 122 and 256 kg m 3 by means of small-angle X-ray scattering (SAXS). The relevant structural parameters are the specific surface area, which is determined by the size of the compact primary particles, the mean diameter of the secondary particles, which represent the building blocks of the gel network, and finally the size of the macropores within the tenuous tertiary structure. The major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Using nitrogen sorption van Nordstrand et al [4] observed in the early fifties a dominant shrinking of macropores and only a small decrease in specific surface area during the beginning of the sintering process. This result has been verified by our group using small angle X-ray scattering to probe the nanostructure [5,6]. Hereby, the specific surface as a function of the pore volume has been found to be the decisive parameter, which easily allows to decide between different model scenarios.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Using nitrogen sorption van Nordstrand et al [4] observed in the early fifties a dominant shrinking of macropores and only a small decrease in specific surface area during the beginning of the sintering process. This result has been verified by our group using small angle X-ray scattering to probe the nanostructure [5,6]. Hereby, the specific surface as a function of the pore volume has been found to be the decisive parameter, which easily allows to decide between different model scenarios.…”
Section: Introductionmentioning
confidence: 62%
“…Assuming arbitrary pore size distributions it is useful to plot the specific surface versus the ratio pore volume over solid volume (Ve/Vs = ~b -1 -1) [5]. In this representation, uniform shrinkage of pores of all size shows up in a linear relationship; a steeper decrease indicates preferential sintering of micropores and vice versa.…”
Section: Theorymentioning
confidence: 99%
“…While the surface areas extracted from NAD generally are consistent with data derived via other methods (e.g., SAXS (8) and TEM (9)), the total pore volume significantly failed to be fully detected for samples with porosities above 85 to 90% (10). Several mechanisms have been proposed to account for the discrepancy between the total specific pore volume V pore,total as calculated from bulk (ρ B ) and skeletal (ρ S ) densities of the sample (V pore,total = 1/ρ B − 1/ρ S ) and the one determined via NAD:…”
Section: Introductionmentioning
confidence: 63%
“…The isothermal densification kinetics of aerogels have been found to fit the Scherer' model (cylinder model) [6,17,18], with viscosity as the only fitting parameter. This model describes viscous flow sintering of amorphous material over a wide range of porosity (0-95%).…”
Section: Sintering By Viscous Flow: the Cylinder Modelmentioning
confidence: 99%